ANALYSIS OF FINANCIAL STATEMENTS USING THE TREND METHOD AS A BASIS FOR ASSESSING THE CONDITION OF THE COMPANY PT. GUDANG GARAM TBK. - Joshua Yugo Hasan; Dedi Mulyadi; Santi Pertiwi Hari Sandi (SEAN Institute, 2022)
This study aims to determine the condition of the company looking at the report of PT Gudang Garam Tbk using metode trend analysis. Gudang Garam is one of the leading cigarette industries in the country which has been established since 1958 in the city of Kediri, East Java. Now, Gudang Garam is well-known both domestically and as a producer of high-quality kretek cigarettes. The data analysis method used is descriptive analysis using calculations to quantitative data in the form of financial reports. Results Based on trend analysis when viewed from the number of assets at PT. Gudang Garam Tbk in 2018-2021 is declared good because its value tends to increase. Based on trend analysis on liability items at PT. Gudang Garam Tbk in 2018-2021 is stated to be in poor condition because the amount of liabilities tends to increase, when viewed from the equity of PT Gudang Garam Tbk, it is considered good because it can increase the amount of equity. increases from year to year but because the total cost of goods sold which also increases exceeds the percentage of sales, the gross profit of PT Gudang Garam Tbk tends to decrease from year to year. Because the company is less effective and efficient in managing all its assets. PT. Gudang Garam Tbk, must be able to reduce the cost of goods sold in order to generate maximum profit.